Drama Korea Dan Penggunaan Media Ilegal Di Kalangan Remaja - Novia Herawati; Silvie Alvionita Safitri; Desderia CIndy Tandiayu (Journal Social Politica, 2021)
The purpose of this study was to find out how the Korean drama phenomenon to the use of illegal media among Indonesian teenagers. The study used a qualitative approach by using the methods of collecting observations, interviews, and literature review. Korean dramas are the belle of Korean Wave products that have been loved by Indonesian teenagers since the 2000s. The emergence of streaming media and downloading Korean dramas such as Netflix, Viu, and Iflix is evidence of the rapid development of digitalization technology. The limitations of legal media that are difficult to access by all circles of society make teenagers look for alternative ways to still be able to watch their favorite Korean dramas, namely through streaming media and illegal downloads. A media is said to be illegal when the platform circulates a film product without the knowledge of the producer or an official contract. The factors that encourage teenagers to access illegal media as a means of watching Korean dramas are; (1) without subscription fees, (2) freedom in accessing content, (3) habits or habits, (4) internet network access. In addition to the legal sanctions already listed in Law no. 28 of 2014 concerning Copyright, various impacts are caused when teenagers misuse illegal media, such as: the user's device will be exposed to viruses, the leaking of user's personal data, and several other terrible things.